Health Insurance (IntechOpen, 2023)
Health insurance is the mechanism used to cover medical expenses for illness, injuries, and other health conditions. There are a variety of health insurance systems in the world. A major challenge for low- and middle-income countries is the provision of universal health coverage (UHC), which is the United Nations’ Sustainability Development Goal Target 3.8.This book examines issues of providing UHC in different health systems around the world, with examples from the Philippines, Portugal, Nigeria, Slovenia, and the United States.